2008
DOI: 10.1029/2007ja012925
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of ionospheric signatures of plasmaspheric plumes over different longitudinal sectors

Abstract: Plasmaspheric plumes have ionospheric signatures and are observed as storm‐enhanced density (SED) in global positioning system (GPS) total electron content (TEC). These ionospheric signatures have been primarily observed over the American sector and in a few limited examples over the European sector. This study examines the longitudinal occurrence frequency of plasmaspheric plumes. We analyzed all images from the Imager for Magnetopause‐to‐Aurora Global Exploration (IMAGE) Extreme Ultraviolet Imager (EUV) data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
(43 reference statements)
0
23
1
Order By: Relevance
“…TEC signatures of plumes are more common in the North American sector, though weaker plume signatures are seen over Europe and Asia (Yizengaw et al 2008). It has been demonstrated that plumes play a crucial role in midlatitude ionospheric density enhancements (Yizengaw et al 2006), polar ionization patches (Su et al 2001) and are strongly correlated with the loss of ring current ions (Burch et al 2001b).…”
Section: Plasmaspheric Plumesmentioning
confidence: 95%
See 1 more Smart Citation
“…TEC signatures of plumes are more common in the North American sector, though weaker plume signatures are seen over Europe and Asia (Yizengaw et al 2008). It has been demonstrated that plumes play a crucial role in midlatitude ionospheric density enhancements (Yizengaw et al 2006), polar ionization patches (Su et al 2001) and are strongly correlated with the loss of ring current ions (Burch et al 2001b).…”
Section: Plasmaspheric Plumesmentioning
confidence: 95%
“…These effects are especially pronounced over the Americas and Foster et al (2005) suggested that this results from a strengthening of the equatorial ion fountain due to electric fields in the vicinity of the South Atlantic Anomaly. Yizengaw et al (2008) demonstrated that EUV observes plumes at all longitudes, but that TEC signatures of plumes are more common in the North American sector, though weaker plume signatures are seen over Europe and Asia. This study and many earlier demonstrate that plumes are most often observed in the aftermath of enhanced geomagnetic activity (not just geomagnetic storms as defined by some minimum Dst value) and that they tend to ap- pear at earlier LT with an increase of geomagnetic activity.…”
Section: The Plasmasphere-ionosphere Connectionmentioning
confidence: 95%
“…The development is caused by the injection of plasmasheet particles into the inner magnetosphere associated with an enhanced convection electric field in the magnetosphere via a reconnection process between the southward interplanetary magnetic field (IMF) and Earth's magnetic field (e.g., Tsurutani et al, ). The enhanced convection electric field leads to a dramatic effect on the dynamics of the ionosphere and plasmasphere such as the formation of a plasmaspheric plume (e.g., Goldstein & Sandel, ; Moldwin et al, ; Yizengaw et al, ) and its ionospheric signature (e.g., Foster et al, , ; Foster & Rideout, ; Yizengaw et al, , ). The convection electric field produces a plasma density enhancement in the ionosphere with a narrow structure which is named storm‐enhanced density (SED; Foster, ).…”
Section: Introductionmentioning
confidence: 99%
“…The high-altitude plasmapause maps to the equatorward edge of the mid-latitude ionospheric trough (Foster et al 1978;Yizengaw & Moldwin 2005). Enhanced storm-time density structures are monitored by GPS total electron content (TEC) techniques and incoherent scatter radars and are the low altitude signatures of drainage plumes (Foster et al 2002;Yizengaw et al 2008).…”
Section: Introductionmentioning
confidence: 99%